SELF-ESTEEM PADA REMAJA TUNANETRA DI BALI - Indrayani, Ni Putu Ananda Putri; Immanuel, Aria Saloka (Jurnal Psikologi Poseidon, 2023)
Abstract. Visual impairment defined as an individual whose senses of sight cannot function properly as a channel for obtaining visual information. Visually impaired persons, including visually impaired adolescents, must continue to fulfil their developmental tasks and carry out activities as normal individuals. Therefore, one of the important internal factors in influencing individual personality is needed, namely self-esteem. This study aimed to determine (a) the categorization of self-esteem levels among visually impaired adolescents in Bali and (b) the influence of sociodemographic variables: gender, visual condition, age of onset, stage of developmental age, level of education, and socioeconomic status. The subjects in this study were 64 visually impaired adolescents, aged 10 to 22 years in Bali. This research was a descriptive quantitative study with a self-esteem scale. The results showed that the majority of participants, as many as 39 people, had high levels of self-esteem and all sociodemographic variables analyzed in this study had no significant effect on self-esteem (p > 0.05). The results of this research are expected to provide theoretical knowledge of psychology as well as practical knowledge for related parties such as visually impaired adolescents, parents, and educational institutions in effort to form and increase self-esteem in visually impaired adolescents.